1975
DOI: 10.1677/joe.0.0660239
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Clearance Rate, Production Rate, and Mammary Uptake and Metabolism of Progesterone in Cows

Abstract: Tracer kinetic techniques have been used to measure the production rate, metabolic clearance rate and mammary uptake of progesterone in six experiments on two Jersey cowsmthe cows were surgically prepared so that the carotid artery, jugular vein and mammary vein concentrations of progesterone, and udder blood flow, could be determined in conscious animals without anaesthesia or stress. The mean production rate of progesterone was 173 +/- 23-3 (S.ET) mug/min, with values ranging from 80 to 276 mug/min in pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

1977
1977
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 18 publications
3
9
0
Order By: Relevance
“…I). These data and other findings [5,8,9] suggest that the metabolic role of the mammary gland is not great and that milk P4 concentration may have been influenced by milk fat content and also the body mass.…”
Section: Resultssupporting
confidence: 64%
“…I). These data and other findings [5,8,9] suggest that the metabolic role of the mammary gland is not great and that milk P4 concentration may have been influenced by milk fat content and also the body mass.…”
Section: Resultssupporting
confidence: 64%
“…Several authors reported a strong influence of the lipid content of cows' milk on P4 concentrations in mammary secretions [50,[54][55][56]. Indeed, after centrifugation of cows' milk, about 80% of P4 is recovered in cream, showing a high affinity of P4 for milk fat [54,57]. In the present study, concentrations of P4 were about 4 times higher in colostrum than in plasma until the end of parturition, which was in agreement with data obtained in cows [50].…”
Section: Comparison Of Hormone Concentrations In Plasma and Other Fluidsmentioning
confidence: 99%
“…Laing and Heap (1971) first reported that estimating the progesterone concentration in milk might provide a method for early pregnancy diagnosis. Absorption of milk progesterone by the mammary gland has been demonstrated in several species (Heap and Linzell, 1966;Heap et al, 1975) and the progesterone level in milk reflects the plasma concentration (Ginther et aL, 1974;Hoffmann et al, 1976). Many workers have reported the use of pregnancy tests based on assaying the level of milk progesterone employing radioimmunoassay (RIA) in cattle ( Van de Wiel et aL, 1978Booth et al, 1979) and milk progesterone determinations have been widely used as a way of monitoring the function of the corpus luteum (Pennington et aL, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Many workers have reported the use of pregnancy tests based on assaying the level of milk progesterone employing radioimmunoassay (RIA) in cattle ( Van de Wiel et aL, 1978Booth et al, 1979) and milk progesterone determinations have been widely used as a way of monitoring the function of the corpus luteum (Pennington et aL, 1976). As progesterone has high solubility in lipids and passes into milk fat, whole milk has higher and more variable progesterone concentrations than fat-free milk (Heap et al, 1975).…”
Section: Introductionmentioning
confidence: 99%